First Nature. The Problem of Nature in the Phenomenology of Merleau-Ponty - Rotundo, Alessio (Studies in Contemporary Phenomenology, 2023)
This book explores a radically integrative phenomenology of nature through the work of Maurice Merleau-Ponty. By revisiting novel empirical findings in the sciences and advances in scientific methods and concepts, Merleau-Ponty leads us to rediscover a first nature right at the heart of the subject. Alessio Rotundo traces and documents the presence of a double meaning of nature affecting Merleau-Ponty's analyses across foundational aspects of human experience: sense perception, organic development and behavior, cognition, language, and history. Physical, biological, and psychological processes in nature are not merely scientific data; they provide the evidence for another, more primordial sense of nature.